2019
DOI: 10.1039/c9sc03610e
|View full text |Cite
|
Sign up to set email alerts
|

A model for dinitrogen binding in the E4state of nitrogenase

Abstract: Molybdenum nitrogenase is one of the most intriguing metalloenzymes in nature, featuring an exotic ironmolybdenum-sulfur cofactor, FeMoco, whose mode of action remains elusive. In particular, the molecular and electronic structure of the N 2 -binding E 4 state is not known. In this study we present theoretical QM/ MM calculations of new structural models of the E 4 state of molybdenum-dependent nitrogenase and compare to previously suggested models for this enigmatic redox state. We propose two models as possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
155
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(160 citation statements)
references
References 93 publications
(73 reference statements)
5
155
0
Order By: Relevance
“…This problem of high HF exchange functionals deteriorating the electronic structure of nitrogenase cofactors has been noted previously by us and others for FeMoco. 51 , 98 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem of high HF exchange functionals deteriorating the electronic structure of nitrogenase cofactors has been noted previously by us and others for FeMoco. 51 , 98 …”
Section: Resultsmentioning
confidence: 99%
“…Our protocol accounts for the protein environment via a systematically improvable QM/MM model and describes the electronic structure via broken-symmetry DFT (BS-DFT) calculations using the TPSSh exchange-correlation functional, which we have found to describe the complex electronic structure of the cofactor better than other functionals. 51 Furthermore, we have shown that the calculated structures are highly sensitive to the redox state of the cofactor and that the charge state of FeMoco could be unambiguously determined by the structural comparison. The analysis furthermore indicated a specific electronic state (BS determinant) to be in better agreement with the experimental structure than the other low-lying states.…”
Section: Introductionmentioning
confidence: 92%
“…In one of these, Ryde et al 2 got results suggesting that the TPSS functional 3 does reproduce the experimental findings for E4, the key species in N 2 activation by nitrogenase. In the other one, Björnsson et al 4 showed that the TPSSh functional 5 might also work. The suggested E4 structures were obtained after only four reductions.…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that all DFT functionals should have a similar problem for the suggested E4 structure. In the two recent theoretical studies by Ryde et al 2 and Björnsson et al 4 of the E4 state, the energetics of that step was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…But ≡C-O(H) coordination with molybdenum of chelated R-homocitrate is still suspicious in view of protons are almost always invisible in limited resolutions of crystal structures, and severe lack of experimental evidence in addition to computational researches 25,26 . The protonation step confers a certain degree of lability to the homocitrate ligation to the cofactor 18,[27][28][29] , and thus allows structural flexibility that is important for the mechanism of N 2 reduction. Recent capture of N 2 species in FeMo-protein confirmed proton translocation and facilitate a serial of hydrogenation like α-hydroxy group 30 .…”
mentioning
confidence: 99%